Application of an employment contract for a trial period in the light of EU and national regulations - Matyjas-Łysakowska, Paulina; Maroń, Anna (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
On July 11, 2019, Directive 2019/1152 of June 20, 2019 on transparent and predictable working conditions in the EU was published. It replaced Directive 91/533/EEC on the employer’s obligation to inform employees of the conditions applicable to the contract or employment relationship of 14 October 1991. Directive 2019/1152 establishes minimum standards for informing employees about the essential aspects of the employment relationship and working conditions and guarantees all employees an adequate level of transparency and predictability of future employment conditions. The prepared study presents the assumptions of the directive with regard to a contract for a trial period and the method of implementing these assumptions adopted in the act amending the Labor Code act of March 9, 2023 amending the Labor Code and certain other acts (Journal of Laws, item 641). The latest changes to the Labor Code, which entered into force on April 26, 2023, pursuant to the Act of March 9, 2023 amending the Labor Code Act and certain other acts, are aimed at, among others: implementation of Directive (EU) 2019/1152 of the European Parliament and of the Council of 20 June 2019 on transparent and predictable working conditions in the European Union.